1997
DOI: 10.1177/112067219700700302
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Hyperlaxity and Obstructive Sleep Apnea (O.S.A.) Syndrome

Abstract: Our study of 69 patients found an association between O.S.A. and eyelid hyperlaxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
2
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 9 publications
4
60
2
10
Order By: Relevance
“…37 The low prevalence in ours and Geyer et al's studies could be the effect of CPAP treatment. Whereas, most other studies reporting higher prevalence of glaucoma in OSAHS (7.2-27%) 3,[6][7][8]28,38 have investigated patients at time of referral for polysomnography and before initiation of therapy; Geyer recruited patients earlier diagnosed with OSAHS and possibly receiving treatment. The authors, however, have not mentioned the treatment status of the OSAHS patients in their report.…”
Section: Discussionmentioning
confidence: 99%
“…37 The low prevalence in ours and Geyer et al's studies could be the effect of CPAP treatment. Whereas, most other studies reporting higher prevalence of glaucoma in OSAHS (7.2-27%) 3,[6][7][8]28,38 have investigated patients at time of referral for polysomnography and before initiation of therapy; Geyer recruited patients earlier diagnosed with OSAHS and possibly receiving treatment. The authors, however, have not mentioned the treatment status of the OSAHS patients in their report.…”
Section: Discussionmentioning
confidence: 99%
“…44 TUAS hastasından 1 (%2,3) 'inde GGS tespit etmiş ve yaş ve beden kitle indeksi ile düzeltme yaptıklarında TUAS ile korelasyon bulamamışlardır. 13,15,16 McNab ve ark. 20 kişiden oluşan hasta gruplarında 3 (%15), hastada Kadyan ve ark.…”
Section: Discussionunclassified
“…10,12,14 TUAS hastalarında GGS görülme sıklığı ise %2-%32 arasında değişen oranlarda bildirilmiş-tir. 3,15,16 Göz kapağı hiperlaksitesi görülme oranları ise GGS görülme oranlarından daha yüksek olup, %29-65 düzeylerindedir. 17 Çalışmamızda, nöroloji kliniği uyku bozuklukları merkezinde polisomnografik inceleme sonrasında TUAS tanısı almış hastalarda göz kapağı laksitesinde değişim, GGS varlığı ve hastalık şiddeti ile oküler bulgular arasındaki ilişkinin araştırılması hedeflenmişdir.…”
unclassified
See 1 more Smart Citation
“…12 Recently, two reports studying the floppy eyelid syndrome in OSAS suggested an association between glaucoma and OSAS. 13 Current studies showed that OSAS was associated with glaucoma and it may be a risk factor for glaucoma. [15][16][17] The prevalence of glaucoma in the OSAS populations has been investigated in several studies and glaucoma prevalence was found between 3.3% and 27%.…”
mentioning
confidence: 99%